The Gay Culture in I Told Sunset About You Series as Depicted by Teh and Oh-Aew’s Character - Alda Shavira Ramadhani; Luly Prastuty (Universitas Brawijaya, 2020)
Lesbian, gay, bisexual, and transgender are referred to as LGBT. LGBT includes a range of gender identities and sexual orientations. Gay means liking the same gender (men) or homosexuals. This article aims to learn about gay culture represented by the two main characters, Teh and Oh-Aew, in the series titled I Told Sunset About You (2020). The characterization theory from Joseph M. Boggs and Dennis W. Petrie was applied with the qualitative method in the data source to collect and analyze the data. This article aims to demonstrate the gay culture that the main character represents. Based on their portrayals, Teh and Oh-Aew demonstrate that they are gay. There are two positions in a gay relationship: the top role is more superior and masculine, while the bottom is more inferior and feminine. Teh has a top role in a gay relationship in the series I Told Sunset About You (2020), and Oh-Aew as a bottom. In conclusion, Teh shows the gay culture by changing his appearance into a more masculine one by styling his hair and changing his clothes to attract Oh-Aew's attention. On the other hand, Oh-Aew also shows the gay culture when he meets Teh by using accessories and woman's clothes. Therefore, the writer hopes this article will enrich the readers’ knowledge to raise understanding of the gay culture.